Status Gizi Dan Perkembangan Pada Anak Baduta Di Kabupaten Wonosobo - Hadi Ashar; Yusi Dwi Nurcahyani; Dyah Yunitawati; Hastin Dyah Kusumawardani (Pusat Penelitian dan Pengembangan Humaniora dan Manajemen Kesehatan, 2021)
The need for nutritional intake in early childhood is not just to maintain survival with the predicate of good nutritional status, but more than that lack of nutritional intake will affect the child's developmental status. This study aims to determine the relationship of characteristics, nutritional status with development status in children aged 6-20 months. The study was conducted in Wonosobo Regency in 2019 with a Cross Sectional design. The population was children aged 6-20 months with sub-districts as the sampling unit. The total sample was 455 of children under two years in one district, but only 450 under two years met the data requirements. The results of the study showed that 19.8% of children under two years were stunted; 27.1% of children experienced motoric development delay; 16.2% of children endured language development delay and 68.7% of children had personal social development delay. Chi-Square test results showed that age was significantly related to motoric and language development with p=0.00; but there was no relationship with social personal development (p=0.50). There was no significant relationship between nutritional status and child development status. In conclusion, age of infants had a significantly higher risk of impaired motor and language development than age above. There was a tendency for boys to have motoric and language development delay. Children who had low birth weight have a risk of personal social development, and WHZ and WAZ nutritional status had a tendency of having language development delay. Abstrak Kebutuhan asupan nutrisi pada anak usia dini tidak hanya sekedar untuk mempertahankan kelangsungan hidup dengan predikat status gizi yang baik, namun lebih dari itu asupan gizi yang kurang akan mempengaruhi status perkembangan anak. Studi ini bertujuan untuk mengetahui hubungan karakteristik, status gizi dengan status perkembangan pada anak baduta usia 6–20 bulan. Studi dilakukan di Kabupaten Wonosobo tahun 2019 dengan desain Cross Sectional. Populasi adalah baduta usia 6-20 bulan dengan sampling unitnya adalah kecamatan. Sampel total sebanyak 455 baduta di satu kecamatan, namun hanya 450 baduta yang memenuhi syarat kelengkapan data. Hasil studi menemukan sebesar 19.8% baduta mengalami stunting; 27.1% mengalami hambatan perkembangan motorik; 16.2% hambatan perkembangan bahasa dan 68.7% mengalami hambatan perkembangan personal sosial. Hasil uji Chi-Square menunjukkan usia berhubungan secara signifikan dengan perkembangan motorik dan bahasa dengan nilai p=0.00; namun tidak terdapat hubungan dengan perkembangan personal sosial (p=0.50). Tidak terdapat hubungan yang signifikan antara status gizi dan status perkembangan anak. Kesimpulan dalam studi ini bahwa usia bayi secara signifikan mempunyai risiko lebih tinggi terhadap gangguan perkembangan motorik dan bahasa dibandingkan usia diatasnya. Terdapat kecenderungan anak laki-laki memiliki risiko hambatan perkembangan motorik dan bahasa, anak yang BBLR memiliki risiko terjadi hambatan perkembangan personal sosial, dan status gizi WHZ dan WAZ terdapat kecenderungan untuk mengalami hambatan perkembangan bahasa.